Legal Certainty of Complete Systematic Land Registration in Resolving Overlapping Ownership Rights Disputes - Aslan Noor; Yayat; Nur Shofa Hanafiah; Ali Husen Al Ansori; Joan Valeria Karina Ongkor (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
. Complete Systematic Land Registration, known as Pendaftaran Tanah Sistematis Lengkap (PTSL), constitutes a strategic government policy intended to accelerate the registration of all land parcels and provide legal certainty and protection for land right holders. Nevertheless, its implementation may still give rise to overlapping-certificate disputes when the collection, examination, mapping, and integration of physical and juridical data are not conducted accurately. This study aims to identify the factors causing overlapping certificates in the implementation of PTSL, analyse their juridical implications for the evidentiary strength of land certificates, and formulate a dispute-resolution mechanism capable of achieving substantive legal certainty in land administration. This study employs normative legal research using statutory, conceptual, and case approaches and adopts a descriptive-analytical design. Secondary data consisting of primary, secondary, and tertiary legal materials were collected through library research. Limited observations and interviews conducted at the Bandung Land Office were used as supporting data to contextualise the implementation of legal norms in practice. The data were analysed through qualitative juridical analysis using grammatical, systematic, and teleological interpretation. The findings demonstrate that overlapping certificates in PTSL are caused by inaccurate physical data, inadequate examination of the history of rights acquisition, incomplete integration of older certificates into the cadastral mapping system, ineffective application of the contradictio delimitatio principle, limited effectiveness of public data announcements, and weak administrative coordination and quality control. A land certificate constitutes strong but not absolute evidence and may be annulled when its issuance is proven to contain an administrative or juridical defect. In principle, the certificate issued earlier has a stronger evidentiary position, provided that it was lawfully issued, remains valid, refers to the same physical object, and was acquired in good faith. Overlapping-certificate disputes should be resolved progressively through verification of physical and juridical data, field re-surveying, cadastral overlay mapping, mediation, administrative correction or annulment, and proceedings before the District Court or State Administrative Court according to the legal character of the dispute. Strengthening data validation, integrating historical land records, and implementing quality control at every stage of PTSL are essential prerequisites for achieving substantive legal certainty in land administration.